2008
DOI: 10.1590/s1517-83822008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal suscepitibility profile of candida spp. oral isolates obtained from denture wearers

Abstract: Denture stomatitis is an inflammatory condition that occurs in denture wearers and is frequently associated with Candida yeasts. Antifungal susceptibility profiles have been extensively evaluated for candidiasis patients or immunosupressed individuals, but not for healthy Candida carriers. In the present study, fluconazole, itraconazole, voriconazole, terbinafine and 5-flucytosin were tested against 109 oral Candida spp. isolates. All antifungal agents were effective against the samples tested except for terbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
10
1
5
Order By: Relevance
“…Our study showed that, C. albicans generate relatively low fluconazole MICs (6.1 μg/ml) compared with C. glabrata ( 8.04 μg/ml ) which has been reported to often generate considerably high fluconazole MICs [34]. This fluconazole MIC value is by far too high compared with a recent study from Brazil where 90% of the isolated Candida species were inhibited by fluconazole at a concentration of 2.0 μg/ml [35]. The frequency of resistance to ketoconazole and itraconazole was relatively lower and found to be 6.6% and 4.4%, respectively with MIC between 0.03–4.0 μg/ml and 0.5–8 μg/ml for ketoconzole and itraconazole, respectively which is comparable with other studies [8,28,35].…”
Section: Discussioncontrasting
confidence: 67%
“…Our study showed that, C. albicans generate relatively low fluconazole MICs (6.1 μg/ml) compared with C. glabrata ( 8.04 μg/ml ) which has been reported to often generate considerably high fluconazole MICs [34]. This fluconazole MIC value is by far too high compared with a recent study from Brazil where 90% of the isolated Candida species were inhibited by fluconazole at a concentration of 2.0 μg/ml [35]. The frequency of resistance to ketoconazole and itraconazole was relatively lower and found to be 6.6% and 4.4%, respectively with MIC between 0.03–4.0 μg/ml and 0.5–8 μg/ml for ketoconzole and itraconazole, respectively which is comparable with other studies [8,28,35].…”
Section: Discussioncontrasting
confidence: 67%
“…Batista et al 26 studied isolates from patients with total dentures and observed good fungistatic activity of amphotericin B with MIC values ranging from 0.03 -0.15 µg/ml. Lyon et al 22 reported a MIC 90 value of 1.0 µg/ml for all isolates, regardless of whether they were taken from denture wearers or individuals with natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Embora estudos com isolados de infecções recidivadas não sejam frequentes, a comparação com a resistência encontrada em outros estudos demonstrou o elevado percentual caracterizado em nosso estudo. Lyon et al (12) , em estudo com indivíduos sadios no estado de Minas Gerais, observaram, num total de 109 isolados de Candida spp., cerca de 10% de resistência ao fluconazol e inibição completa pela anfotericina B. Embora na amostragem os indiví-duos não apresentassem sinais de candidíase e muito menos alguma deficiência imunológica predisponente, observava-se uma nítida diferença nos percentuais de resistência, considerando que as amostras em nosso estudo são também de indivíduos sadios, mas com candidíase oral diagnosticada e isolados após recidiva da doença. De forma semelhante aos resultados observados no perfil de suscetibilidade aos isolados de origem oral, nos testes realizados com cepas de infecções recidivadas de candidíase vaginal, obtidas de pacientes imunocompetentes, a resistência foi de 100% para anfotericina B e para o fluconazol, e cerca de 93% para o miconazol.…”
Section: Discussionunclassified
“…O perfil de sensibilidade de Candida spp. aos antifúngicos não é o mesmo nas diferentes populações ou comunidades, o que torna fundamental a identificação do agente etiológico causador da candidíase antes de iniciar a terapêutica empírica, bem como a realização do antifungigrama em alguns indivíduos para conhecer e monitorar a resistência a esses fármacos na população que é atendida (12) . Devido à importância clínica desse tema, e sobretudo à ausência de estudos sobre a avaliação da suscetibilidade aos antifúngicos de cepas oriundas de candidíase oral ou vulvovaginal no estado de Santa Catarina, esse estudo teve por objetivo realizar uma investigação do perfil de resistên-cia aos antifúngicos anfotericina B, fluconazol e miconazol, fármacos usualmente encontrados nas prescrições desta região do Brasil.…”
Section: Introductionunclassified